EVALUATION OF THE BRINE PRESERVATION METHOD OF SEA GRAPES (Caulerpa lentillifera) AS A COMMERCIAL PRODUCT - Imran Lapong; Nicholas Paul; Akbar Reza (Marina Chimica Acta, 2019)
The aim of this study is to evaluate this commercial product in relation to the preservation materials, the preserved product biomass, individual weight and length of the fronds, and the effect of soaking time and water temperatures on the frond “crispiness”. There was no significant difference between different soaking times (from 30s to 2 minutes) on the weight and the length of the fronds ANOVA (p=0.88) and (p=0.81) after the initial period. Furthermore, tap water and ice water treatments during rehydration process had no significant effect on the fronds crispiness (ANOVA p=0.560). These results show that the preserved product using high concentration of brine produces a product with consistent biomass, size, and amount of the fronds. However, the temperature of the freshwater used in rehydration has no effect on the quality of the product, in contrast to the claims made by the company on the packaging instructions